2020
DOI: 10.1111/1742-6723.13608
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence in emergency departments: The health professionals and security personnel alliance

Abstract: Violence in the health sector is a widespread worldwide phenomenon. Emergency nurses and emergency physicians are among the most exposed. In violent incidents, security personnel also play an important role. Wand and colleagues on Emergency Medicine Australasia have tried to give voice to the opinions and experiences of security personnel in responding to aggression and behavioural problems. Sharing some data from our 2016 Italian National Survey on Violence towards Emergency Nurses, further elements are provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…52 Similarly Ramacciati et al 9 called for "suitable environments with adequate structural measures"; however, this largely amounted to official security measures such as police presence and cameras. 9,53 As such there is growing awareness about how the ED environment can contribute or compound ED violence. The phenomenon of being "forced to wait" 54 is now more clearly understood as stressful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Similarly Ramacciati et al 9 called for "suitable environments with adequate structural measures"; however, this largely amounted to official security measures such as police presence and cameras. 9,53 As such there is growing awareness about how the ED environment can contribute or compound ED violence. The phenomenon of being "forced to wait" 54 is now more clearly understood as stressful.…”
Section: Discussionmentioning
confidence: 99%
“…Although the provision of TV, newspapers, and magazines was also discussed 52 . Similarly Ramacciati et al 9 called for “suitable environments with adequate structural measures”; however, this largely amounted to official security measures such as police presence and cameras 9,53 . As such there is growing awareness about how the ED environment can contribute or compound ED violence.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also identified differences in doctors understandings of violence as a barrier to prevention and management 12 . There is also emerging knowledge about the interaction between healthcare workers and security staff and its impacts on violence prevention and management 21 . Programmes regarding violence education, reporting and responding to violence at all levels could be improved.…”
Section: Discussionmentioning
confidence: 99%
“…12 There is also emerging knowledge about the interaction between healthcare workers and security staff and its impacts on violence prevention and management. 21 Programmes regarding violence education, reporting and responding to violence at all levels could be improved.…”
Section: Societal and Organisational Culturementioning
confidence: 99%
“…Workplace violence (WPV) is a universal problem that threatens the health and safety of workers (Ramacciati and Giusti, 2020). Indeed, Lanctôt and Guay (2014) revealed the different sectors affected by this pandemic, such as those of healthcare settings, transport, education and commerce.…”
Section: Introductionmentioning
confidence: 99%